(untitled) (Research, Society and Development, 2021)
Intro: Every year, thousands of adverse events occur in health care, and 2/3 of these incidents are caused by human error. Despite the ethical obligation, such errors are not commonly disclosed and the practice of effective communication with patients and families is largely neglected. Objective: to analyze the use of disclosure, as a tool for quality and safety management, among health professionals and patients. Method: The method used was a systematic review, submitted and published in the Prospero, using the databases pubmed, scielo, lilacs and bvs. The keywords used for the search were "disclosure", "medical errors" and "patient safety". Results: 13 articles were analyzed and it was possible to evidence punctually the categories named: medical errors and patient safety, processes and protocols and state of the art. Conclusion: the disclosure process does not receive enough attention in the scientific community or in health institutions around the world, considering that few countries have formalized and institutionalized practices through protocols or guidelines on this technique of effective communication primarily human.